High prevalence of diabetes and anthropometric heterogeneity among tuberculosis patients in Pakistan. Issue 4 (23rd February 2017) - Aftab, Huma; Ambreen, Atiqa; Jamil, Mohammad; Garred, Peter; Petersen, Jørgen H.; Nielsen, Susanne D.; Bygbjerg, Ib C.; Christensen, Dirk L.
Abstract: Background: In Pakistan, the prevalence of diabetes (DM) among adults is 6.9% and expected to double by 2040. DM may facilitate transmission and halter the elimination of tuberculosis (TB). We aimed to determine the prevalence of DM among patients with TB in Pakistan, and to investigate anthropometric biochemical and haemodynamic associations between TB patients with and without DM. Methods: We conducted a cross‐sectional study at Gulab Devi Chest Hospital in Lahore, Punjab. A total of 3027 newly diagnosed smear‐positive TB patients ≥25 years of age were screened for DM by HbA1c regardless of previous DM history. Results: The prevalence of screen‐detected DM and known DM among the TB participants was 13.5% and 26.1%, respectively, resulting in a combined DM prevalence of 39.6%. Most participants were male (64.4%). Using bivariate analyses, participants with DM were significantly older (49.8 vs . 40.6 years) with higher haemoglobin (men, 12.1 vs . 11.8 g/dl, women 11.5 vs . 10.7 g/dl), body mass index (21.0 vs . 17.6 kg/m 2 ) and waist–hip ratio (men, 0.87 vs . 0.81, women, 0.87 vs . 0.79) (all P < 0.05) than participants without DM. Stratifying by screen‐detected and known DM, these differences remained significant when using multivariate analysis. Conclusion: We report a high prevalence of DM among patients with TB who may be anthropometrically and biochemically distinct from TB patients without DM, and this heterogeneity further transcends the different DM groups.